2015
DOI: 10.1007/s10646-015-1590-x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of hydroxymethylfurfural (HMF) on mortality of artificially reared honey bee larvae (Apis mellifera carnica)

Abstract: Hydroxymethylfurfural (HMF) is a heat-formed, acid-catalyzed contaminant of sugar syrups, which find their way into honey bee feeding. As HMF was noted to be toxic to adult honey bees, we investigated the toxicity of HMF towards larvae. Therefore we exposed artificially reared larvae to a chronic HMF intoxication over 6 days using 6 different concentrations (5, 50, 750, 5000, 7500 and 10,000 ppm) and a control. The mortality was assessed from day 2 to day 7 (d7) and on day 22 (d22). Concentrations ranging from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(41 citation statements)
references
References 43 publications
1
35
0
3
Order By: Relevance
“…Except for these small-scale studies, few studies have systematically examined the effect of HMF on bee health and physiology, which is surprising given that concentrations of 7500 ppm HMF (mg/kg) or higher have been reported to cause massive bee kills, i.e., 100% mortality of bee larvae with LC 50 for larvae ranging from 2424 ppm to 4280 ppm. Thus, larvae appear far more sensitive to HMF than adult honey bees [26]. Clearly, our results coupled with evidence cited earlier confirm the toxicity of HMF to adult and developing honey bees and the need for its mitigation in commercial bee yards.…”
Section: Discussionsupporting
confidence: 86%
“…Except for these small-scale studies, few studies have systematically examined the effect of HMF on bee health and physiology, which is surprising given that concentrations of 7500 ppm HMF (mg/kg) or higher have been reported to cause massive bee kills, i.e., 100% mortality of bee larvae with LC 50 for larvae ranging from 2424 ppm to 4280 ppm. Thus, larvae appear far more sensitive to HMF than adult honey bees [26]. Clearly, our results coupled with evidence cited earlier confirm the toxicity of HMF to adult and developing honey bees and the need for its mitigation in commercial bee yards.…”
Section: Discussionsupporting
confidence: 86%
“…In another study, a sugar solution containing 30–150 mg/kg of HMF was used to feed honey bees and was found to cause 15–58.7% of deaths of caged bees within 20 days [ 78 ]. Krainer et al [ 88 ] reported that the LD50 values of HMF for bee larvae fed for more than 6 days were 4280 and 2424 mg/kg on days 7 and 22, respectively. Interestingly, they found that 7-day larvae emerging after being fed HMF for 6 days were more sensitive than were adult bees, but the emerging adult bees at day 22 were less sensitive.…”
Section: Hazard Posed By Hmf To Honey Beesmentioning
confidence: 99%
“…One of the basic disadvantages of the readyto-use foods used in feeding bees, irrespective of the food type (inverted sucrose, starch) is the content of 5-hydroxymethylfurfural, also called HMF, which is harmful for bees (Jachimowicz & El Sherbiny, 1975;LeBlanc et al, 2009). This compound is created in the production process of these foods, and the amount of this compound depends on the temperature and acidity of the environment (Krainer et al, 2016). A high concentration of HMF in products used to feed bees can upset the proper functioning of bee colonies (Van der Zee & Pisa, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…The amount of food provided to bees, is a one-time dose and the time of supplying winter supplementation is an important element of the so-called winter feeding of bee colonies (Pidek, 1985;Severson & Erickson, 1984;Seeley & Visscher, 1985;Pedersen, Pedersen, & Pedersen, 1996;Skubida, 1998). To supply winter food, beekeepers can use sugar syrup, sucrose inverted syrup, starch syrup or high-fructose corn syrup (HFCS) (Jachimowicz & El Sherbiny, 1975;Skubida, 1998, von der Ohe & Schönberger, 2002Liebig, 2005;Ceksteryte & Racys, 2006;LeBlanc et al, 2009;Brodschneider & Crailsheim, 2010, Sammataro & Weiss, 2013Krainer at al., 2016). Sugar syrup (a mixture of water and pure sucrose from sugar beets or sugarcane) has been used for many years to feed honeybees (Free & Spencer-Booth, 1961;Barker, 1971;Bobrzecki, 1976;Gromisz, 1985).…”
Section: Introductionmentioning
confidence: 99%